KOMUNIKASI MANAJERIAL KEPALA SEKOLAH DALAM PENJAMINAN MUTU PENDIDIKAN (Studi Situs SMP Negeri 3 Polanharjo Klaten) - Rahmah , Ratnasari Nur (2011)
Purpose of research is description characteristic communications managerial headmaster, guarantee quality of education, and communications managerial headmaster in guarantee quality of education. This research approach is qualitative research, is research about data collected and expressed in the form of words compiled in sentence. Research approach applies phenomenology. Research subject is committee chief, headmaster, and teacher. Data collecting method applies in-depth interview, observation, and documentation. Analysis data analytical technique interactive. authenticity of data applies trianggulation technique. Result of research that is : a headmaster vertical communications system is communications with its(the superior wanting existence of repair of school quality through enableness of source and good school potencies in the form of physical , organization energy , and public area around school with aim to increase quality of school especially output from itself school. Horizontal communications of headmaster is communications sesame headmaster in striving guarantee quality / quality of education of be a concordance / conformity between goodness and service with standard which has been specified to fulfill requirement so that creation of customer satisfaction. School makes an attempt on guarantee quality of education to orient at consumer, there is emphasis at designing and management process quality of education is responsibility of all organization pays attention to sigh from consumer so that always tries to increase quality of education. Downward communication of Headmaster in guarantee quality of education is an activity of manage organization school focusing, first time, for customer? client and the its(the dealers. Total quality management in organization, all people is customer? client and dealer. This concept emphasizes at systematic of work experiencing where all entangled. Equally, cooperation a group and collaborative is interest becomes habit, education tends to collective, and common interest.